Fabrication And Performance Analysis Of Bi2te3 And Sb2te3 Thin Film Thermoelectric Generator For Waste Heat Recovery - Nurfarhana Ahmad Musri; Yoganash Putthisigamany; Puvaneswaran Chelvanathan; Norasikin Ahmad Ludin; Nadhrah Md Yatim; Ubaidah Syafiq (Cerebration Science Publishing, 2025)
Hybridizing thermoelectric generators (TEGs) with renewable energy systems offers a promising route to enhance energy efficiency. However, conventional bulk TEG modules are bulky and impractical for applications requiring lightweight and flexible designs, such as building-integrated systems. This study addresses this limitation by developing a thin film TEG using stoichiometric bismuth telluride (Bi₂Te₃) and antimony telluride (Sb₂Te₃) deposited on a glass substrate via radio frequency magnetron sputtering. The structural, morphological, and thermoelectric properties of the films were analyzed using XRD, FESEM, EDX, Hall effect, and Seebeck coefficient measurements, confirming their suitability for device fabrication. The fabricated TEG, consisting of 6 n-type Bi₂Te₃ and p-type Sb₂Te₃ pairs, achieved a maximum open-circuit voltage of 208.55 mV and power output of 0.54 µW at a temperature difference of 125 K, with a maximum power per unit active planar area of 0.1 µW cm⁻². These results demonstrate the feasibility of thin film TEGs for integration into lightweight and compact energy-harvesting systems, highlighting their potential in renewable energy applications.